Advances in seed mucilage: Chemical characterization, functional properties, extraction, and applications in edible coatings for meat preservation - Bernardo D. Tobar-Espinoza; José R. Pérez-Correa (Applied Food Research)
Seed mucilage represents a diverse group of plant-derived biopolymers with significant potential in food preservation applications due to their unique functional properties and natural origin. The preservation of refrigerated meat products faces significant challenges due to lipid oxidation and microbial growth, which degrade quality and shorten shelf life. Seed mucilage-based edible coatings provide an eco-friendly alternative to synthetic preservatives. This review examines advanced mucilage extraction techniques, including ultrasound and microwave-assisted methods, and emerging approaches utilizing deep eutectic solvents. It also explores cutting-edge analytical methods for mucilage characterization, such as FTIR, NMR, HPLC, and electron microscopy, offering insights into its chemical structure and functional properties. Emphasis is placed on the relationship between mucilage's molecular structure and its functional attributes, including water retention, gel formation, bioadhesion, and encapsulation of bioactive compounds like essential oils and antimicrobial agents. Recent research demonstrates that seed mucilage-derived coatings can extend the shelf life of refrigerated meat by reducing lipid oxidation, inhibiting microbial growth, and maintaining sensory and nutritional qualities. The bioadhesive and barrier properties of mucilage enhance the controlled release of active ingredients, effectively retarding spoilage. This review highlights the potential of seed mucilage as a natural, cost-effective, and sustainable solution to meat preservation challenges, addressing the growing demand for environmentally responsible packaging while ensuring product quality and safety.